“Unveiling the Cinematic Artistry: Pedagogical Approaches to Teaching Spaghetti Westerns in Higher Education” - Marco Lettieri (RiCognizioni)
This article proposes interdisciplinary approaches, utilizing film theory, cultural studies, and historical perspectives to facilitate an enriched learning experience for students by  examining the socio-political contexts, directorial styles, and thematic elements prevalent in Spaghetti Westerns. The Spaghetti Westerns genre can be useful in the context of teaching Italian culture, cinema, and language, due to the genre’s ability to transcend traditional genre boundaries, subvert expectations, and provide a candid commentary on society. The best Spaghetti Westerns movies allow students to question longstanding myths of American heroism and reflect the disillusionment of Italian society with its own political realities. Moreover Italian curricula in North American Universities should give to Spaghetti Westerns more attention because while the study of neorealist films in a second language classroom may be beneficial in terms of exploring narration and character development, Spaghetti Westerns are better in terms of discussions regarding innovative cinematic techniques.